Level of school anxiety of girls aged 12-13 years old with different kinds of postural - Tamozhanskaya, A.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose : to identify the level of school anxiety of girls with signs of normal, round-shouldered, lardotic, kyphotic and straightened by the types of carriages during a school year. Material : the study involved 137 girls 12-13 years old. Was held diagnostics level of school anxiety Phillips. Results : It was found that girls with normal posture there is a general anxiety in school, fear of the situation knowledge test. With stooping - frustration needs to succeed, fear of self-expression. With lardotic - frustration needs to succeed, fear of self-expression. With kyphotic - general anxiety at school, frustration needs to succeed, fear not meet the expectations of others. With straight - manifestation of the general emotional state, negative attitudes and experience of anxiety in the situation knowledge test. Conclusions : factors of school anxiety have different effects on girls. It was established that during adolescence the need to integrate and correction of psychological state and the musculoskeletal system. This is due to the formation of morphological features, formation of character traits.